SERTIFIKASI DAN PENGELOLAAN TANAH WAKAF DI KECAMATAN GUNUANG OMEH KABUPATEN LIMAPULUH KOTA PROVINSI SUMATERA BARAT - Vito Dasrianto (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
The certification and management of waqf land was written based on the results of research in the field, namely in Kecamatan Gunang Omeh, Limapuluh Kota, West Sumatra. Bbased on the number of waqf lands used to support the public interest and welfare of the people, so the central function of waqf land in the area. All of the waqf lands should be recorded neatly and the archives can be found at the local Religious Affairs Office as a whole, in this case all the waqf lands should have been recorded and certified for better management, while things like that have not been realized as desired so that In the future, the waqf land will be more productive than the previous one and will no longer cause problems, both in terms of the person who gave the waqf and the Nazir as the manager of the waqf land. So that the management of waqf land is in accordance with the waqf pledge and the waqf land runs according to its function.